Microcirculation imaging - Leahy, Martin J. (Weinheim : WiVCH ; Chichester : John Wiley [distributor], 2012)
Adopting a multidisciplinary approach with input from physicists, researchers and medical professionals, this is the first book to introduce many different technical approaches for the visualization of microcirculation, including laser Doppler and laser speckle, optical coherence tomography and photo-acoustic tomography. It covers everything from basic research to medical applications, providing the technical details while also outlining the respective strengths and weaknesses of each imaging technique. Edited by an international team of top experts.
Microcirculation Imaging; Contents; Preface; List of Contributors; 1 A Historical Perspective of Imaging of the Skin and Its Gradual Uptake for Clinical Studies, Inclusive of Personal Reminiscences of Early Days of Microcirculation Societies; 1.1 Early History; 1.2 The Microcirculatory Societies; 1.3 A Tour of Microcirculatory Centers in 1968; 1.4 TV Video Projection; 1.5 The Third World Congress of Microcirculation; 1.6 Perfusion Monitoring and the Advent of the Laser Doppler; 1.7 3D and 4D Tomographic Methods; 1.8 Nonoptical Microcirculation Imaging.
Includes bibliographical references.
Print version record.
Keywords: Cardiovascular system -- Imaging; Microcirculation; MEDICAL -- Cardiology; Cardiovascular system -- Imaging; Microcirculation; Electronic books